Internalisasi Nilai Musyawarah/Mufakat Melalui Pembelajaran Sosiologi Berbasis Kearifan Lokal Duduk Adoik - Irda Yusepa; Wilodati Wilodati; Siti Komariah (Universitas Pendidikan Mandalika, 2022)
This study aims to describe the internalization of the value of deliberation/consensus through Sociology learning based on the local wisdom of Duduk Adoik at SMA Negeri 5 Sungai Penuh. This study involved a qualitative approach with a case study method. The selection of informants was made by using the purposive sampling technique. The data collection techniques observed a series of learning activities conducted by the teacher in the classroom. The interviews were conducted by asking structured and open questions to the informants, and the last technique was the study of documentation. The data analysis was carried out through data condensation, data display, and conclusion drawing. This study also used data triangulation techniques to test the data's validity: observation, in-depth interviews, and documentation. The result of the research showed that the value of deliberation/consensus through Sociology learning based on the local wisdom of Duduk Adoik had been internalized in SMA Negeri 5 Sungai Penuh City by using a role-playing learning model. Students play the role of Duduk Adoik in class through role-playing. They animate the roles in Duduk Adoik and the procedure for implementing deliberation in making decisions so that the value of Duduk Adoik can be internalized within students.